Analysis of oil sludge and selection of solvents for the extraction method of petroleum products recovery - Panova, Ye.S.; Issabayev, Ye.A.; Baigaziyev, M.T.; Boiko, G.I.; Lyubchenko, N.P.; Sarmurzina, R.G. (KSU Publ., 2018)
Analysis of oil sludge formed in a storage tank for straight-run fuel oil of «Pavlodar Oil Chemistry Refinery» LLP was carried out in this work. Content of water, oil products and mechanical impurities was 12.4 %, 17.6 % and 70 %, respectively. A sample of oil separated from the sludge was analyzed for the content of silica gel resins, paraffins and asphaltenes, and their group composition was studied using the IR spectrometry method. It was revealed that the oil sludge stabilizers belonged to the paraffin type. TG/DSC analysis was used to obtain information on the initial and final temperature of the thermal decomposition of the oil sludge. It was shown that oil products are completely burned to a temperature of 600 ºC. This temperature was used for calcining oil sludge. The phase composition of mechanical impurities isolated from the oil sludge was determined by X-ray diffraction analysis. According to the data obtained from X-ray diffraction analysis, main constituents of the mineral part of the oil sludge were quartz sand (63.1 %) and albite (16.5 %). The most optimal mixture of solvents (white spirit: hexane) for extracting petroleum products from the oil sludge was obtained using the extraction method.
Мұнай өнімдерін экстракциялық əдіспен бөліп алу үшін мұнай шламын талдау жəне еріткіштерді таңдау
Анализ нефтяного шлама и подбор растворителей для экстракционного метода извлечения нефтепродуктов
Keywords: oil sludge; mechanical impurities; solvent; extraction; paraffins; resins; aspTG/DSC analysishaltenes